Enhancement in seed production of Pearlspot, Etroplus suratensis (Bloch) through improvisation in rearing techniques. Issue 3 (3rd July 2022) - Pradeep, B.; Manoj, K. K.; Ratha Krishnan, P.
ABSTRACT: Three seed production techniques of pearlspot Etroplus suratensis (Bloch)—pond rearing, tank rearing, and pit rearing—were evaluated in farmers' fields to assess production success, practicality, and economic viability. The pond rearing technique stocked mature pearlspot in ponds with artificial substrates and reared seed in the pond itself. The tank rearing technique collected pearlspot eggs from the pond and hatched and reared them in separate tanks. The pit rearing technique trapped pearlspot fry using a specially designed falling trap and reared them in ponds with an artificial feed. The average fingerlings productions per spawning per pair were 47 ± 27, 93 ± 22, and 578 ± 82 respectively. The pit rearing technique was reported to be preferred by farmers because of its ease and cost effectiveness. The homing instinct of pearlspot brooders with spawn to the nursing pits was observed even weeks after hatching.